2019
DOI: 10.1128/jvi.01334-18
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Presentation of Skin-Targeted Recombinant Adeno-associated Virus 2/1 Transgene Induces Potent Resident Memory CD8 + T Cell Responses

Abstract: A key aspect to consider for vaccinal protection is the induction of a local line of defense consisting of nonrecirculating tissue-resident memory T cells (TRM), in parallel to the generation of systemic memory CD8+ T cell responses. The potential to induce TRM has now been demonstrated for a number of pathogens and viral vectors. This potential, however, has never been tested for recombinant adeno-associated virus (rAAV) vectors, which are weakly inflammatory and poor transducer of dendritic cells. Using a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Several studies highlighted the usefulness of certain AAV serotypes for immunomodulation and cancer vaccines, depending on capsid configuration, dose, and route of administration in a mouse model 14, 15, 16, 17, 18, 19. Among other serotypes, AAV6 is able to transduce the cells of myeloid origin in general 39 , 69 and DCs in particular 25 , 35 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies highlighted the usefulness of certain AAV serotypes for immunomodulation and cancer vaccines, depending on capsid configuration, dose, and route of administration in a mouse model 14, 15, 16, 17, 18, 19. Among other serotypes, AAV6 is able to transduce the cells of myeloid origin in general 39 , 69 and DCs in particular 25 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies highlighted the usefulness of certain AAV serotypes for immunomodulation and cancer vaccines, depending on capsid configuration, dose, and route of administration in a mouse model. [14][15][16][17][18][19] Among other serotypes, AAV6 is able to transduce the cells of myeloid origin in general 39,69 and DCs in particular. 25,35 Thus, AAV6-based vectors with Ova as a model Ag as described here are a highly attractive platform for developing anti-tumor vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 , 16 Other groups have shown that the AAV1 serotype can be used for vaccine development. 13 , 17 , 18 While AAV1 is generally a poor transducer of APCs, the intradermal route of immunization activates cross-presenting APCs against transgenes expressed in mouse skin. The combination of intradermal injection and fusion of Ag with male HY Ag epitopes, which additionally provides CD4 + T helper cells in female mice, ensured the generation of functional Ag-specific cytotoxic T cells against model Ag ovalbumin (OVA).…”
Section: Introductionmentioning
confidence: 99%